Cardioselective beta-adrenoreceptor blockade with betaxolol in cardiovascular therapy - D. V. Duplyakov (Кардиоваскулярная терапия и профилактика)
Beta-adrenoreceptor blockers are widely used in the treatment of various cardiovascular diseases. The review discusses the benefits of a highly selective beta-adrenoblocker betaxolol in patients with coronary heart disease, arterial hypertension, cardiac arrhythmias, and chronic heart failure. Possible adverse effects are also discussed, including metabolic, bronchial, and lactation-related ones.